Competências gerenciais de professores-gestores no contexto da pós-graduação: uma análise sob a perspectiva de coordenadores de cursos da Universidade Federal da Paraíba - Frade, Cinthia Moura (2020)
In the context of federal public universities, administrative positions, such as the coordination of courses, are usually occupied by professors from the institution itself, revealing the role of the teacher-manager in higher education. However, managerial activities do not require the same competencies from the teacher regarding the research, extension and teaching exercise, which requires the mobilization of different competencies in the face of the activities performed. For the above, this study had as general objective to understand the development of managerial competencies of the professor-manager in the context of postgraduate studies at the Federal University of Paraíba (UFPB) based on the perspective that these professionals perform activities with high responsibility. Thus, the path covered involves stages of research of a qualitative nature and exploratory character, through the use of the method of oral history and application of narrative interviews with fifteen coordinators of stricto sensu postgraduate courses of Campus I of UFPB. The treatment of the data and the analysis took place from the narrative analysis, allowing the identification of dimensions and categories, some already preestablished, others emerged from the data, with this, it was possible to point out elements that drive the development of managerial competences in the post-graduation professor-manager. The results revealed that the majority of the teacher-managers assumed the management without interest, had no previous preparation and feel limitations in the development of management activities due to lack of training in the area of management, as a consequence, the learning occurs in the daily activities. The findings showed that teacher-managers mobilize cognitive, functional, behavioral and political competencies, with greater repercussion around political capacities. In general, the coordinators claimed an accumulation of duties that transcended the workload, they claimed an environment of pressure, due to the demands of the higher authorities, in particular CAPES, in the face of the evaluations that determine the maintenance of the program in this system, they also showed relational difficulties, especially with teachers, in the face of egos and conflicts existing in the environment and also showed dissatisfaction with the challenges arising from limitations of financial resources and scholarships, as well as the lack of infrastructure. Thus, the presented panorama allowed to outline the need for interventions by the UFPB in relation to investments that can better prepare teachers, both with regard to managerial activity, as for facing different questions that revealed an unstable environment in which the teacher-manager acts.